The readiness of schools in Zimbabwe for the implementation of early childhood education - Mangwaya, Ezron; Blignaut, Sylvan; Pillay, Shervani K. (2016)
This qualitative study focuses on primary schools’ state of readiness for the introduction of early childhood education. Adopting a multiple case study design, the article explores, through semi-structured interviews and documentation, school heads, teachers-in-charge and classroom teachers’ perceptions of their respective schools’ state of readiness for the installation and implementation of early childhood education. The study established that, while classroom teachers were adequately qualified to implement early childhood education, teachers-in-charge were not. Secondly, school heads received limited induction for the introduction and implementation of early childhood education. Additionally, inadequate teaching-learning resources and lack of on-going teacher support contributed to schools’ lack of readiness for the introduction of early childhood education. The study recommends interventions that curriculum planners and implementers can utilise in order to create conditions that enable primary schools to be ready for introducing and implementing early childhood education.